A honlapok értékelésének szempontrendszere - Harsányi, Dávid; Máté, Zoltán; Zarándné Vámosi, Kornélia (Vezetéstudomány / Budapest Management Review, 2021)
Websites are usually the basis for businesses’ online presence. The authors’ goal was to create a comprehensive evaluation system that can be applied without training, thus helping businesses to develop their own websites. Online testing sites and competitions are of limited use to smaller businesses. Therefore, after reviewing the secondary sources, they conducted 12 expert interviews with senior professionals, based on which the topics and factors of website evaluation were identified. This allowed for the development of a 100-point system. This solution is a novel opportunity for digitally less mature companies with a limited financial and professional background, providing objective feedback about their website and highlighting the shortcomings and the necessary directions for development. The system can thus educate small and medium sized enterprises (SMEs) and is also suitable for comparison with competitors.